Techniques for Non-Invasive Monitoring of Arterial Blood Pressure - Meidert, Agnes S.; Saugel, Bernd (Frontiers in Medicine, 2018)
Since both, hypotension and hypertension, can potentially impair the function of vital organs such as heart, brain, or kidneys, monitoring of arterial blood pressure (BP) is a mainstay of hemodynamic monitoring in acutely or critically ill patients. Arterial BP can either be obtained invasively via an arterial catheter or non-invasively. Non-invasive BP measurement provides either intermittent or continuous readings. Most commonly, an occluding upper arm cuff is used for intermittent non-invasive monitoring. BP values are then obtained either manually (by auscultation of Korotkoff sounds or palpation) or automatically (e.g., by oscillometry). For continuous non-invasive BP monitoring, the volume clamp method or arterial applanation tonometry can be used. Both techniques enable the arterial waveform and BP values to be obtained continuously. This article describes the different techniques for non-invasive BP measurement, their advantages and limitations, and their clinical applicability.